2016
DOI: 10.1002/jhet.2596
|View full text |Cite
|
Sign up to set email alerts
|

Iodine/Water Mediated Parallel Synthesis of Bioactive Diversely Substituted Pyrazolo‐Pyrido‐Pyrimidines and Its Spiro Analogues: An Enviro‐Economic Approach

Abstract: A convenient, green, and efficient protocol for the synthesis of diversely substituted pyrazolo‐pyrido‐pyrimidines has been described by a simple one‐pot four‐component reaction of hydrazine, ethyl acetoacetate, 6‐amino‐1‐methyluracil, and isatin or aldehyde catalyzed by iodine in water. Environmental friendliness, operational simplicity, low cost, high yields, and applicability to a wide range of readily available starting materials are the key features of this methodology. Most importantly, workup of this ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A convenient, eco-friendly, and efficient method for making a diverse range of pyrazolo-pyridopyrimidines 89-93 was conducted by Sagir and co-workers in 2016. [98] This simple one-pot, four-component reaction used hydrazine 79, ethyl acetoacetate 78, 6-amino-1-methyluracil 92, and either isatin 87 or aldehyde 2, with iodine as a catalyst in water. The main benefits of this approach include environmental friendliness, ease of operation, low cost, high yields, and compatibility with a wide variety of easily available starting materials.…”
Section: Inorganic-catalyzed Synthesis Of Pyrido[23-d]pyrimidine Comp...mentioning
confidence: 99%
“…A convenient, eco-friendly, and efficient method for making a diverse range of pyrazolo-pyridopyrimidines 89-93 was conducted by Sagir and co-workers in 2016. [98] This simple one-pot, four-component reaction used hydrazine 79, ethyl acetoacetate 78, 6-amino-1-methyluracil 92, and either isatin 87 or aldehyde 2, with iodine as a catalyst in water. The main benefits of this approach include environmental friendliness, ease of operation, low cost, high yields, and compatibility with a wide variety of easily available starting materials.…”
Section: Inorganic-catalyzed Synthesis Of Pyrido[23-d]pyrimidine Comp...mentioning
confidence: 99%
“…Furthermore, performing the reaction in the aqueous medium was also advantageous for the separation of the product which could be possible just by filtration because of the solubility-difference of the product from the reactants. It was also perceived that the different isatin derivatives containing electron donating/electron withdrawing groups smoothly offered the The workup of the reaction involved only filtration and chromatography or recrystallization was not needed 95 .…”
Section: Scheme 40 Ring Formation Reaction In Acidic Solutionmentioning
confidence: 99%
“…The workup of the reaction involved only filtration, and chromatography or recrystallization was not needed. 95…”
Section: Synthesis Of Fused Pyrazoles In Water Using­ a Catalystmentioning
confidence: 99%
“…Various iodine catalyzed multicomponent protocols for the synthesis of pyrimidine derivatives were reported in the literature. Sagir et al [63] . reported a molecular iodine catalyzed one‐pot four‐component synthesis of pyrazolo‐pyrido‐pyrimidines 54 (Scheme 28).…”
Section: Iodine Catalyzed/mediated Multi‐component Reactionsmentioning
confidence: 99%
“…Various iodine catalyzed multicomponent protocols for the synthesis of pyrimidine derivatives were reported in the literature. Sagir et al [63] reported a molecular iodine catalyzed one-pot four-component synthesis of pyrazolo-pyrido-pyrimidines 54 (Scheme 28). Hydrazine, ethyl benzoylacetate, 6amino-1-methyluracil, and isatin were reacted in water at 90 °C using molecular iodine (10 mol %) giving the desired product.…”
Section: Synthesis Of Various Functionalized Pyridines Piperidines Py...mentioning
confidence: 99%